2020
DOI: 10.3390/su12135259
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Innovation through Joining Global Supply Chain Networks: The Case of Manufacturing Firms in Thailand

Abstract: Joining global supply chain networks helps firms to enhance innovation performance as firms need to satisfy various standard requirements from overseas customers. From the global value chain theory, there is no evidence on what types of supply chain ownership structures help firms to achieve more innovation. This deficiency led us to investigate types of supply chain ownership structures, i.e., Pure Domestic Chain, Pure Joint Venture (JV) Chain, Pure Multinational Corporation (MNC) Chain, Export Chain, and Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…According to them, a high degree of visibility is only possible when the core elements namely, people, technology, and process work in synchronously. Kimseng, Javed, Jeenanunta, & Kohda (2020) argue that the key advantages of visibility in the supply chain are the increase in market efficiency in general, which serves as a foundation for better decision-making, both at strategic and organizational levels. According to them, firms benefit from proper visibility of the supply chain at a functional level by having the capacity to modify the supply chain swiftly and effectively, an ability that is becoming extremely relevant in quickly changing market conditions and which creates a competitive advantage.…”
Section: Supply Chain Visibilitymentioning
confidence: 99%
“…According to them, a high degree of visibility is only possible when the core elements namely, people, technology, and process work in synchronously. Kimseng, Javed, Jeenanunta, & Kohda (2020) argue that the key advantages of visibility in the supply chain are the increase in market efficiency in general, which serves as a foundation for better decision-making, both at strategic and organizational levels. According to them, firms benefit from proper visibility of the supply chain at a functional level by having the capacity to modify the supply chain swiftly and effectively, an ability that is becoming extremely relevant in quickly changing market conditions and which creates a competitive advantage.…”
Section: Supply Chain Visibilitymentioning
confidence: 99%
“…In contrast, visibility is a likely outcome of information sharing practices [49][50][51]. The key advantages of exposure in the supply chain are the general increase in market efficiency, offering a foundation for better decision-making, both at strategic and organizational levels [52,53]. Organizations benefit from proper visibility of the supply chain at a functional level by having the capacity to reconfigure the supply chain rapidly and effectively [54].…”
Section: Supply Chain Visibilitymentioning
confidence: 99%
“…Ma and Rauf (2020) found that foreign knowledge spillover channels can drive export performance more effectively than domestic innovation channels. Kimseng et al (2020) argued that the knowledge exchange in the global value chain system can help enterprises to carry out innovative activities. Rigo (2020) believed that foreign technology spillovers in the global value chain system can help local enterprises to increase their productivity.…”
Section: Literature Reviewmentioning
confidence: 99%